Existence Results for Fractional Semilinear Integrodifferential Equations of Mixed Type with Delay - Xue Wang; Bo Zhu (Journal of Function Spaces)
In this paper, we discuss a class of fractional semilinear integrodifferential equations of mixed type with delay. Based on the theories of resolvent operators, the measure of noncompactness, and the fixed point theorems, we establish the existence and uniqueness of global mild solutions for the equations. An example is provided to illustrate the application of our main results.